2020
DOI: 10.3390/ijms21155344
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Hormone Biosynthetic and Metabolism Genes in the 2OGD Family for Identifying Genes That May Be Involved in Tomato Fruit Ripening

Abstract: Phytohormones play important roles in modulating tomato fruit development and ripening. The 2-oxoglutarate-dependent dioxygenase (2OGD) superfamily containing several subfamilies involved in hormone biosynthesis and metabolism. In this study, we aimed to identify hormone biosynthesis and metabolism-related to 2OGD proteins in tomato and explored their roles in fruit development and ripening. We identified nine 2OGD protein subfamilies involved in hormone biosynthesis and metabolism, including the gibberellin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…RNA binding proteins and serine-type endopeptidase inhibitor-related genes were identified, and previous studies revealed involvement in the regulation of flowering time ( Steffen et al, 2019 ; Zhang F. et al, 2019 ). In addition, genes functionally annotated as 2-oxoglutarate-dependent dioxygenase, drug transmembrane transport, antiporter activity, pyridine nucleotide biosynthetic process, and chromatin assembly or disassembly were associated with fruit ripening in tomato, apricot, grape, peach, apple, and strawberry ( Hanana et al, 2007 ; Farinati et al, 2017 ; Decros et al, 2019 ; Ding et al, 2020 ; García-Gómez et al, 2020 ). Furthermore, previous studies have shown that molybdopterin cofactor plays an important role in the metabolic control of avocado fruit growth and final fruit size ( Cowan et al, 2001 ) and ion/H+ exchanger genes (GO: ion transmembrane transport) were critical for providing pH regulation ( Pittman, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA binding proteins and serine-type endopeptidase inhibitor-related genes were identified, and previous studies revealed involvement in the regulation of flowering time ( Steffen et al, 2019 ; Zhang F. et al, 2019 ). In addition, genes functionally annotated as 2-oxoglutarate-dependent dioxygenase, drug transmembrane transport, antiporter activity, pyridine nucleotide biosynthetic process, and chromatin assembly or disassembly were associated with fruit ripening in tomato, apricot, grape, peach, apple, and strawberry ( Hanana et al, 2007 ; Farinati et al, 2017 ; Decros et al, 2019 ; Ding et al, 2020 ; García-Gómez et al, 2020 ). Furthermore, previous studies have shown that molybdopterin cofactor plays an important role in the metabolic control of avocado fruit growth and final fruit size ( Cowan et al, 2001 ) and ion/H+ exchanger genes (GO: ion transmembrane transport) were critical for providing pH regulation ( Pittman, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…As is described in the background section above, the 37 Vv2OGD-Hs are functional in six hormones biosynthesis and metabolism, GAs, IAA, ET, JAs, SAs and SLs [ 6 ]. Previous studies have proved that these six hormones play irreplaceable roles in fruit ripening or fruit quality formation process [ 18 – 20 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The members in DOXB are P4Hs, they participate in the post-translational modification of protein and hydroxylate proline residues by forming 4-hydroxyproline [ 3 ]. DOXC is the largest branch of 2OGD, with 99 and 159 members in Arabidopsis and tomato respectively [ 6 ]. Until now, DOXC members have been found to be involved in hormone biosynthesis or metabolism, and catalyze the synthesis of some secondary metabolites, such as flavonoids, benzylisoquinoline alkaloids, glucosinolates and tropane alkaloids, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations